p ( q − r ) x 2 + q ( r − p ) x + r ( p − q ) = 0
If the equation above has two equal roots, find p 1 + r 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Elegant approach!
p ( q − r ) x 2 + q ( r − p ) x + r ( p − q ) ( r q − 1 ) x 2 + q ( p 1 − r 1 ) x + ( 1 − p q ) = 0 = 0 Divide both sides by p r
For the equation to have two equal roots, the discriminant b 2 − 4 a c = 0 ⟹ b 2 = 4 a c :
q 2 ( p 1 − r 1 ) 2 q 2 ( p 2 1 − p r 2 + r 2 1 ) q 2 ( p 2 1 + p r 2 + r 2 1 ) q 2 ( p 1 + r 1 ) 2 = 4 ( r q − 1 ) ( 1 − p q ) = 4 ( r q − p r q 2 − 1 + p q ) = 4 q ( r 1 + p 1 ) − 4 = 4 q ( r 1 + p 1 ) − 4
⟹ q 2 ( p 1 + r 1 ) 2 − 4 q ( p 1 + r 1 ) + 4 ( q ( p 1 + r 1 ) − 2 ) 2 ⟹ q ( p 1 + r 1 ) p 1 + r 1 = 0 = 0 = 2 = q 2 A quadratic equation of q ( p 1 + r 1 )
It should be "Divide both sides by p r ."
The question is too simple.check that x = 1 is the root so product= 1 ∗ 1 .so r ( p − q ) = p ( q − r ) .now divide by p q r so 1 / p + 1 / r = 2 / q
Did it the same way!
Ya!!this is quite easy.isn't it??
Problem Loading...
Note Loading...
Set Loading...
Given that
p ( q − r ) x 2 + q ( r − p ) x + r ( p − q ) = 0 Comparing above equation with quadratic equation a x 2 + b x + c = 0 we get,
a = p ( q − r )
b = q ( r − p )
c = r ( p − q )
Since the roots are equal so it determinant D = 0 i.e; D = b 2 − 4 a c = 0
Now substituting the value of a , b and c we get
q ( r − p ) ) 2 − 4 ( p r ( q − r ) ( p − q ) ) = 0
q 2 ( r 2 − 2 p r + p 2 ) − 4 ( p r ( p q − q 2 − p r + q r ) ) = 0
q 2 r 2 − 2 p r q 2 + p 2 q 2 − 4 ( p 2 r q − p r q 2 − p 2 r 2 + p q r 2 ) = 0
q 2 r 2 + ( − 2 p r q 2 + 4 p r q 2 ) + p 2 q 2 − 4 ( p 2 r q + p q r 2 ) + 4 p 2 r 2 = 0
( q r + p q ) 2 − 4 ( q r + p q ) p r + ( 2 p r ) 2 = 0
( q r + p q − 2 p r ) 2 = 0
q r + p q = 2 p r
Dividing both p q r we get,
p q r q r + p q r p q = p q r 2 p r
p 1 + q 1 = q 2